The role of beliefs regarding the uncertainty of knowledge and mental effort as indicated by pupil dilation in evaluating scientific controversies. Issue 3 (11th February 2020) - Lang, Fabian; Kammerer, Yvonne; Oschatz, Kerstin; Stürmer, Kathleen; Gerjets, Peter
ABSTRACT: Laypeople are increasingly confronted with scientific controversies, as science concerns many aspects of everyday life. In the present study, we investigated how epistemic beliefs regarding the uncertainty of knowledge (i.e. uncertainty beliefs) and invested mental effort during task processing contribute to how individuals evaluate scientific controversies. Forty-four undergraduate university students completed a questionnaire targeting their uncertainty beliefs and a week later worked on a test that required the evaluation of five scientific controversies. Eye-tracking technology was used to measure participants' pupil dilation while reading the controversies as an indicator of individuals' invested mental effort. Results revealed that both uncertainty beliefs and mental effort were positive predictors of individuals' test performance (i.e. their proficient evaluation of the controversies). Furthermore, uncertainty beliefs predicted mental effort. Finally, a mediation analysis revealed that mental effort partially explained the relation between uncertainty beliefs and test performance. We discuss implications of how individuals' epistemic beliefs regarding the uncertainty of knowledge influence the evaluation of conflicting scientific information through mental effort, offering both theoretical clarification and practical recommendations.